(NpERSIDSKIE MOTIWY(B:s (NlIRIKAs - (NeSENIN s(B. (Na(B.s ((NsERGEJ aLEKSANDROWI^(B)s; e ((NtO[KENT(B:s (NiZDATELXSTWO LITERATURY I ISKUSSTWA IMENI gAFURA gULQMA(B,s, 1996)
"(NpERSIDSKIE MOTIWY(B" (NsERGEQ eSENINA PO PRAWU QWLQ@TSQ [EDEWROM MIROWOJ L@BOWNOJ LIRIKI(B. (NiZDANIE PRIURO^ENO K (B100-(NLETI@ PO\TA(B.s
(NiNW(B.: 1740 (NOB(B/1-2s
(NtIRAV(B: 2000 (N\KZ(B.s
(NNA RUS(B. (NI UZB(B. (NQZYKAHs
Keywords: (NSTIHIs -- (NSTIHOTWORENIQs -- (NRUSSKAQ PO\ZIQs